2002
DOI: 10.1021/ac0205107
|View full text |Cite
|
Sign up to set email alerts
|

A Fluorescent Chemosensor for Sodium Based on Photoinduced Electron Transfer

Abstract: A new optical sensor suitable for practical measurement of sodium in serum and whole blood samples is described. The optical sensor is based on a novel PET (photoinduced electron transfer) fluoroionophore immobilized in a hydrophilic polymer layer. The design concept of the fluoroionophore follows the receptor-spacer-fluorophore approach to sensor design using intramolecular PET-based signal transduction. Key to the development of this sensor is the identification of a nitrogen-containing, sodium-binding ionop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
95
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(96 citation statements)
references
References 19 publications
1
95
0
Order By: Relevance
“…This issue takes on added significance given the growing body of sensors and other optical devices which employ 4-amino-1,8-naphthalimide (or closely related) fluorophores. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Hence, compounds 1-3 and 4-6 were synthesized and tested by steady-state electronic absorption and emission spectroscopy. …”
Section: Introductionmentioning
confidence: 99%
“…This issue takes on added significance given the growing body of sensors and other optical devices which employ 4-amino-1,8-naphthalimide (or closely related) fluorophores. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Hence, compounds 1-3 and 4-6 were synthesized and tested by steady-state electronic absorption and emission spectroscopy. …”
Section: Introductionmentioning
confidence: 99%
“…5,12,13 They absorb around 450 nm and emit in the green, with λ max ~ 550 nm and a high fluorescence quantum yield. Moreover, they are easily synthesized in bulk quantities as well as being well suited for incorporation into polymeric matrixes and onto solid-surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Such hydrogels are easily handled and, when the composition is chosen judiciously, do not require that the sensor be covalently bonded to the polymeric matrix. 5,14,15 Compounds 1 and 2 are examples of our general design. In this paper we give account of our recent results on the synthesis of, as well as the solution and the soft-matter luminescent properties, of 1 and 2 as a function of pH.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Important picosecond laser studies on fluorescent PET sensors/switches have demonstrated the transient existence of radical ion species, [9][10][11] and thus designers can proceed with confidence. As a result of their modular fluorophore-spacer-receptor construction, fluorescent PET systems are very amenable to modification in terms of the format, as well as in terms of the detailed functionalities.…”
mentioning
confidence: 99%